Granulocyte colony stimulating factor versus human chorionic gonadotropin for recurrent implantation failure in intra cytoplasmic sperm injection: a randomized clinical trial - Mohamed Sobhy Bakry; Elsayed Eldesouky; Moatazza Mahdy Alghazaly; Elsayed farag; Eslam Elsayed Kamal Sultan; Hossam Elazzazy; Attia Mohamed; Soliman Mohamed Said Ali; Assem Anwar; Asmaa Ahmed Elrashedy; Mohamed Abdelmonem; Mohamed Abd-ElGawad; et al. (BMC, 2022)
Abstract Background Repeated implantation failure (RIF) is defined as the case whereby the transferred embryos fail to implant after several attempts of In vitro fertilization (IVF) which causes a profound impact on the quality of life and financial burden. Some clinical studies have confirmed that Granulocyte colony-stimulating factor (G-CSF) and human chorionic gonadotropin (HCG) can improve pregnancy outcomes and implantation rates. Hence, our study aims to compare the efficacy of G-CSF and HCG on pregnancy outcomes in RIF women who undergo intra-cytoplasmic sperm injection (ICSI). Methods This randomized, single-blinded study was conducted et al.-Azhar University Hospitals, Cairo, Egypt, between 10th October 2020 and 20th December 2020. The study included 100 women aged 20-43 years old undergoing ICSI cycles, with a history of RIF. Patients were divided randomly into two groups: group (1): included 50 patients injected with 500 IU of intrauterine HCG on embryo transfer day, and group (2): Included 50 patients injected with G-CSF on the embryo transfer day. Results In 100 RIF women, we found a significant improvement in pregnancy outcomes favoring G-CSF over HCG including implantation rate, chemical pregnancy, and clinical pregnancy (P < 0.0001, P = 0.0003, and P = 0.0006, respectively). Conclusion For the first time, we demonstrated a significant improvement in pregnancy outcomes favoring G-CSF over HCG in terms of implantation rate, chemical pregnancy, and clinical pregnancy. Trial registration The study was registered on Pan African Clinical Trials Registry with the following number: PACTR202010482774275 and was approved on 2nd October 2020.